TEACHER´S CONTINUOS EDUCATION: ENVIRONMENTAL EDUCATION EXPERIENCES IN SEMIARID - Hugo da Silva Florentino; Francisco José Pegado Abílio (Editora da Universidade de Santa Cruz do Sul, 2016)
The article aims to describe the studies and pedagogical interventions of environmental education developed in Caatinga biome by continuing education processes of teachers in the municipality of Sumé, Paraíba. It was a qualitative research with emphasis on assumptions of bioregionalism theory, school ethnography and phenomenology. It was developed during the year 2012 with 50 elementary school teachers, and in three steps: (1) diagnosis and intervention demands, (2) continuing education process, and (3) assessment of the obstacles and challenges of research. The results obtained from the teacher diagnosis identified an educational process marked by the lack of teaching resources, infrastructure and continuing education courses in the environmental area. However, the realization of a process of continuing education in environmental education based on participatory, contextualized and interdisciplinary practices, enabled a socio-educational transformation in this schools including environmental education in the pedagogical practice of teachers and the daily life of schools in Sumé.